2016
DOI: 10.1073/pnas.1510847113
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity and tolerance for visual texture in macaque V2

Abstract: As information propagates along the ventral visual hierarchy, neuronal responses become both more specific for particular image features and more tolerant of image transformations that preserve those features. Here, we present evidence that neurons in area V2 are selective for local statistics that occur in natural visual textures, and tolerant of manipulations that preserve these statistics. Texture stimuli were generated by sampling from a statistical model, with parameters chosen to match the parameters of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
151
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(170 citation statements)
references
References 53 publications
(82 reference statements)
13
151
3
Order By: Relevance
“…The biphasic pooling was prominent in the data set (34% of neurons), with uniform pooling observed in the remaining cases. Overall, the observed patterns of selectivity based on locally orthogonal excitatory and suppressive features that are repeated across a range of spatial position could mediate the observed selectivity of V2 responses to textures1718 and texture boundaries132021.…”
Section: Discussionmentioning
confidence: 86%
“…The biphasic pooling was prominent in the data set (34% of neurons), with uniform pooling observed in the remaining cases. Overall, the observed patterns of selectivity based on locally orthogonal excitatory and suppressive features that are repeated across a range of spatial position could mediate the observed selectivity of V2 responses to textures1718 and texture boundaries132021.…”
Section: Discussionmentioning
confidence: 86%
“…For example, the population in Figure 6a is best described using five PCs but only three can be readily visualized at once. In order to visualize PC coefficients in a two-dimensional (2-D) coordinate system we employed the t -distributed stochastic neighboring embedding algorithm ( t -SNE) (Maaten and Hinton, 2008; Ziemba et al, 2016), as shown in Figure 6b ( left ), which differentiate groupings of spines. We then ran a supervised k-means clustering algorithm on the synaptic PCA coefficients in order to cluster spines (see Methods), where the optimal number of clusters was chosen using the Calinski Harabasz score (Caliński and Harabasz, 1974) as the criterion (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 for an example). Recent studies have invigorated the debate in visual neuroscience as to whether form or texture are the primary drivers for visual perception [6, 7**, 8]. For example, often shapes defined by textures are perceived more readily than those based on outlines [8].…”
mentioning
confidence: 99%
“…In the primary visual cortex (V1), neural responses are tuned to specific combinations of angles at specific positions. Presumably this explains why V1 neurons are better at discriminating individual samples with a shared texture than different texture types from each other [7**]. This situation changes in the secondary visual cortex (V2) where neurons trade the ability to distinguish individual samples for their ability to distinguish between different texture types [6,7**].…”
mentioning
confidence: 99%
See 1 more Smart Citation